2000
DOI: 10.1159/000016366
|View full text |Cite
|
Sign up to set email alerts
|

Actin Cytoskeleton: A Signaling Sensor in Cell Volume Regulation

Abstract: The actin microfilaments are well known dynamic structures that support and organize the cell membrane and functions associated with the membrane such as ion channels and transporters. In addition, many aspects of cellular physiology seem to be actively modulated by changes in actin cytoskeleton dynamics, which involve reorganization and restructuring of the filaments. For both of these reasons, the actin cytoskeleton has attracted special attention since the early days of cell volume regulation research. Mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
45
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 38 publications
4
45
0
1
Order By: Relevance
“…The strong adhesive state is characteristic of a differentiated, quiescent cell, whereas cells in the intermediate adhesive state include those involved in responding to injury during wound healing or tissue remodelling (20). Cell shape can regulate cell fate and function (21) and actin cytoskeleton is critical for cell volume (22). In the present study, we found that Id1 protein could induce cell adhesion and spreading.…”
Section: Discussionsupporting
confidence: 48%
“…The strong adhesive state is characteristic of a differentiated, quiescent cell, whereas cells in the intermediate adhesive state include those involved in responding to injury during wound healing or tissue remodelling (20). Cell shape can regulate cell fate and function (21) and actin cytoskeleton is critical for cell volume (22). In the present study, we found that Id1 protein could induce cell adhesion and spreading.…”
Section: Discussionsupporting
confidence: 48%
“…Despite this swelling of cells, other well defined characteristics of apoptosis including chromatin condensation, externalization of the phosphatidylserine, caspase activity, and DNA degradation persisted. Furthermore, maintenance of normal physiologic intracellular ion concentrations has been shown to inhibit caspase activation and apoptotic nuclease activity during programmed cell death (14 -17).The actin cytoskeleton is well recognized to regulate the activity of ion channels and transporters involved in maintaining cellular homeostasis and cell volume (18,19). The importance of ion redistribution during apoptosis has, thus, led us to consider the potential role of the actin cytoskeleton in the cell death program during AVD.…”
mentioning
confidence: 99%
“…The actin cytoskeleton is well recognized to regulate the activity of ion channels and transporters involved in maintaining cellular homeostasis and cell volume (18,19). The importance of ion redistribution during apoptosis has, thus, led us to consider the potential role of the actin cytoskeleton in the cell death program during AVD.…”
mentioning
confidence: 99%
“…The response cascade can be classified into four mechanistic components: volume sensing, signal generation, signal transduction, and effector activation (10). Given that PIP 2 is a multifunctional regulator and adaptor, the PIP 2 increase may coordinate many of the responses to hypertonic stress.…”
mentioning
confidence: 99%